2010
DOI: 10.1093/eurjhf/hfq028
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training improves cardiac function in infarcted rabbits: involvement of autophagic function and fatty acid utilization

Abstract: AimsTo explore whether exercise can improve cardiac function in a post-myocardial infarction (MI) rabbit model and to determine contributing factors in the left ventricle (LV). Methods and resultsAdult male New Zealand White rabbits (2.5 -3 kg) underwent MI by ligation of the left anterior descending coronary artery. For 8 weeks after surgery, sham-operated, and post-MI rabbits were housed under sedentary conditions or assigned to a 4-week treadmill exercise protocol at a speed of 1.0 km/h for 30 min 5 days pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
40
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 44 publications
1
40
0
Order By: Relevance
“…Cardioprotective interventions, such as caloric restriction [11,12] , exercise [13] , and chloramphenicol succinate [14] , have been reported to initiate autophagy. Ischemic preconditioning also induces autophagy to promote cardioprotective effects [15,16] .…”
Section: Introductionmentioning
confidence: 99%
“…Cardioprotective interventions, such as caloric restriction [11,12] , exercise [13] , and chloramphenicol succinate [14] , have been reported to initiate autophagy. Ischemic preconditioning also induces autophagy to promote cardioprotective effects [15,16] .…”
Section: Introductionmentioning
confidence: 99%
“…Iemitsu et al (26) demonstrated that regular exercise in aging rats prevented age-induced decreases in PPAR␣ expression and subsequent age-induced heart dysfunction. Similarly, exercise training improved cardiac function in rabbits with myocardial infarction-induced heart failure; this was associated with greater FA utilization (8). Therefore, changes in the amount or type of substrates for cardiac energy production might prevent or improve heart failure.…”
Section: Discussionmentioning
confidence: 93%
“…This may be attributed to the increase in cardiac mass that occurs with exercise and not changes in cardiac substrate usage (39). Other studies suggest that training improves FA utilization by the heart (8,49). Whether FAs or glucose are needed for both hypertrophy and improved cardiac function is not known.…”
mentioning
confidence: 99%
“…This idea, although speculative, is supported by reports showing that endurance exercise training is accompanied by terminal deoxynucleotidyl-dUTP nick end labelingpositive nuclei and activation of apoptotic mediators (Bax, cytochrome c, cleaved caspase-3, and cleaved PARP) in LV cardiomyocytes (18) as well as enhanced abundance of cardiac progenitor cells (21). In addition, cardiac autophagy has been recently associated with exercise training, with some data pointing to its involvement in exercise-induced cardioprotection (4,40). However, the role of apoptosis and autophagy in the exercised heart is still under debate, and further data are needed to clarify this issue.…”
Section: Discussionmentioning
confidence: 95%